Methycillin-Resistant Staphylococcus Aureus (Mrsa) Pada Ulserasi Septum Nasi - Agus Bayu Dianindra Putra; I Gusti Ayu Dwi Susantini (Syntax Corporation Indonesia, 2023)
Staphylococcus aureus is a gram-positive, which belongs to the Staphylococcus aureus family forming grape-like cluster. Staphylococcus aureus can be found in parts of the human body such as the skin, skin glands, mucous membranes, nose and intestines. Methycillin-resistant Staphylococcus aureus (MRSA) is a Staphylococcus aureus that has mutations in penicillin-binding protein (PBP), namely the mecA gene with decreased affinity for most penicillins. Reported one case of a 59-year-old man with MRSA in nasal septal ulceration. Diagnosis is based on anamnesis, physical examination and laboratory test like complete blood count and antibiotic culture test. The therapy in this case was giving tetracycline 4 x 500mg for 14 days.